Leadership in Realizing Financial Management Accountability for Village-Owned Enterprises - Intiyas Utami; Aprina Nugrahesthy Sulistya Hapsari; Yohanes Yakobus Werang Kean (The Indonesian Accounting Review, 2022)
This study aims to explore the role of leadership in realizing the accountability of financial managment of ecotourism–based BUMDes Au Wula in Detusoko Barat Village, Ende Regency, East Nusa Tenggara Province. This research uses a qualita-tive method with the resource persons consisting of village officials, government representatives, indigenous community leaders, and local community representatives. The data were collected through interviews and focused discussions with various sources regarding the ideal leadership model in managing ecotourism-based Village-Owned Enterprises (Indonesia: Badan Usaha Milik Desa /BUMDes). The results indicate that the type of transformative leadership in BUMDes Au Wula has a role in realizing BUMDes financial management accountability such as a role model, inspirators, stimulator of creativity and inno-vation, and consultant for BUMDes managers. In addition to other supporting documents, BUMDes financial reports can be completed and accounted for properly. Another finding relates to the regeneration of the leadership of BUMDes Chairman when he was then elected as the Head of Detusoko Barat Village.